PENGARUH RADIASI SINAR GAMMA TERHADAP TANAMAN KACANG HIJAU (Vigna radiata L.) PADA KONDISI KEKERINGAN - Jelita Sianipar; Lollie Agustina.P Putri; Syafruddin Ilyas (Universitas Sumatera Utara, 2013)
Demand of mungbean will be increase, so the production must be increased. One of efforts is to create superior variety by giving mutation.The goal of this research is to find out the effect of four level radiation dosage and drought stress to growth and yield of mungbean (Vigna radiata L.), has finished in greenhouse of Agriculture Faculty of North Sumatera University, Medan conducted from May until August 2012. This Research was conducted using by Randomize Block Design factorials.The first factor is radiation dosage with four levels : 0, 10, 20, and 30 krad. The second factors is drought stress: 100%, 80%, 60%,and 40% KL. Data were analyzed with ANOVA and continued with HSD.The result of research showed the radiation significantly affected to the harvesting time. Drought stress significantly affected to the root volume, the number of pod per plant,and weight seeds per plant. The combination between dose of radiation and drought stress significantly affected to flowering time. Key word : mungbean, radiation, drought stress